Facilitating Curriculum Change One Step At a Time - Joanna Mott (Academic Chairpersons Conference Proceedings, 2017)
Large departments provide additional challenges when leading change. Participants will learn strategies to thoughtfully move a department forward keeping transparency, respect for all and inclusiveness in mind and identifying, empowering and guiding department faculty leaders who are trusted by their peers.
Keywords: change; curriculum; diverse faculty; large department; facilitation